2020
DOI: 10.5937/jaes18-24319
|View full text |Cite
|
Sign up to set email alerts
|

Research of ways of connecting reinforced bars in the production of reinforced concrete products

Abstract: The authors conduct research on the creation of non-waste technology for the use of reinforcing bars in the manufacture of reinforced concrete products (reinforced concrete). This article presents the results of a study of existing methods for connecting reinforcing bars in the manufacture of reinforced concrete. The connection methods were investigated: mechanical, lap welded. Their advantages and disadvantages are revealed. Welding methods have also been investigated: contact, bathroom docking, contact spot,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The spent exhaust gas was supplied to the ultrasonic muffler through the inlet pipe 1 at a pressure that depends on the crankshaft speed. In the muffler, with the ultrasonic equipment turned on, the ultrasonic waves a given confidence level, from a specially compiled table of the distribution of the Student's values; f -limiting relative error of the experiment [11].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spent exhaust gas was supplied to the ultrasonic muffler through the inlet pipe 1 at a pressure that depends on the crankshaft speed. In the muffler, with the ultrasonic equipment turned on, the ultrasonic waves a given confidence level, from a specially compiled table of the distribution of the Student's values; f -limiting relative error of the experiment [11].…”
Section: Methodsmentioning
confidence: 99%
“…At the second stage of the experiment, the dependence of the settled soot mass on the sedimentation length L was investigated. Tables 3 to 11 give examples of the experimental results' recordings.…”
Section: Methodsmentioning
confidence: 99%
“…The results of the study [3] were carried out in the conditions of the construction plants of the RK, in particular in the conditions of Powerbeton LLP (Prishakhtinsk city) [4], NORD Prom NS LLP (Temirtau city), ZhBI-5 LLP (Aktas city), Remstroytekhnika JSC (Almaty city), Temirbeton -1 LLP (Almaty city) [5], showed that, depending on the arrangement of production and on the productivity of the production of reinforced concrete products, about 2% of reinforcing steel is wasted [2]. Figure 1 shows a histogram of the percentage of waste reinforcing bars at a construction enterprise.…”
Section: Introductionmentioning
confidence: 99%
“…The studies carried out in the conditions of construction enterprises of the Republic of Kazakhstan, in particular the Karaganda region, have shown that this technology is advisable to use in the manufacture of concrete products such as bar lintels. As a result of the studies carried out [6], [7], [8], [9], a construction of a bar lintel [10] was designed, which is made of a concrete mixture [11] with the addition of man-triggered waste and a space frame [12] whose reinforcing bars are welded from non-dimensional segments of reinforcement. Segments of reinforcing bars were joint by friction welding.…”
Section: Introductionmentioning
confidence: 99%